Simultaneous occurrence of large B-cell non-Hodgkin lymphoma and acute myeloid leukaemia in an elderly patient: complete remissions of both diseases by rituximab-bendamustine regimen combined to hypomethylating therapy. (1st August 2013) - Palombi, Massimiliano; Niscola, Pasquale; Tendas, Andrea; Trawinska, Malgorzata Monika; Scaramucci, Laura; Giovannini, Marco; Fratoni, Stefano; Perrotti, Alessio; Fabritiis, Paolo de
Abstract : The case of an elderly and frail patient affected by simultaneous large B-cell non-Hodgkin lymphoma and acute myeloid leukaemia is reported. The complete remissions of both diseases by azacitidine and rituximab-bendamustine regimen were achieved.